DESIGN AND DEVELOPMENT OF E-ARCHIVE APPLICATION TO IMPROVE THE SERVICE PERFORMANCE OF KANTOR IMIGRASI KELAS III NON TPI KOTABUMI - Muhammad Mukti Adji Adiatmadja; Isidorus Anung Prabadhi (Polteknik Imigrasi, 2020)
The purpose of this papers is to explain the study result of the writer about the design of E-Archive Application for increasing the service performance of Kantor Imigrasi Kelas III Non TPI Kotabumi. Based on the study that writer do, known if archive management system of an Immigration Office can affecting the performance of Immigration Office’s service. The main case that making some troubles is archive management system of Kantor Imigrasi Kelas III Non TPI Kotabumi still not using Paperless system. That thing affect on the employees’s workload and inflicting problems like the long archival search process, obstruction of the Immigration Administrative Sanction and Criminal Act completion process, and even the archival damage because dust, water, or insect. In the development proces, this E-Archive Application will be adjusted with Kantor Imigrasi Kelas III Non TPI Kotabumi’s need. This E-Archive Application be expected to integrated with immigration service Front Desk of Immigration Office and Aplikasi Antrian Paspor Online (APAPO) directly, and can be implemented by Kantor Imigrasi Kelas III Non TPI Kotabumi and another Immigration Office in Indonesia, so that can help increasing and optimizing the service performance of Immigration Offices.